Australian work exposures studies: occupational exposure to pesticides. Issue 1 (8th September 2016) - Jomichen, Jasmine; El-Zaemey, Sonia; Heyworth, Jane S; Carey, Renee N; Darcey, Ellie; Reid, Alison; Glass, Deborah C; Driscoll, Tim; Peters, Susan; Abramson, Michael; Fritschi, Lin
Abstract : Background: Pesticides are widely used in some occupational settings. Some pesticides have been classified as carcinogens; however, data on the number of workers exposed to pesticides are not available in Australia. The main aim of this study was to estimate the current prevalence of pesticide exposure in Australian workplaces. Methods: The analysis used data from the Australian Work Exposures Study, a series of nationwide telephone surveys which investigated work-related prevalence and exposure to carcinogens and asthmagens, including pesticides, among current Australian workers. Information about the respondents' current job and various demographic factors was collected in a telephone interview using the web-based tool OccIDEAS. Workers were considered exposed to pesticides if they reported applying or mixing pesticides in their current job. Results: Of the 10 371 respondents, 410 (4%) respondents were assessed as being exposed to pesticides in the workplace, with exposure being more likely among males, individuals born in Australia, individuals with lower education level and those residing in regional or remote areas. Glyphosate was the most common active ingredient used by workers. Conclusions: This is the first study to describe the prevalence of occupational pesticide exposure in Australia and one of the few recent studies internationally.